Diagnóstico de la producción de artesanía ancestral de los cantones Loja, Gonzanamá y Saraguro de la Provincia de Loja. - Caraguay Satama, María Alexandra (2014)
The choice of this topic " Diagnosing production ancestral craftsmanship of Loja, Gonzanamá and Saraguro cantons of Loja Province " arises from the need of the artisans of the above counties, represented by the Chamber of Artisans the Province of Loja, who proposed research with the aim to propose strategies to progress of these cantons in his craft production. It was considered productive wealth possessed by these three counties, as well as having the skills to residents making crafts , allowing productive participatory development of the sector resulting in the improvement of their quality of life , product diversification and also serve to promote culture possessed by each canton, making viable the progress of the region towards the much desired economic and social development.